Difficulties in mathematical language and representation among elementary school students when solving word problems - Agusfianuddin, Agusfianuddin; Herman, Tatang; Turmudi, Turmudi (Jurnal Elemen, 2024)
Difficulties in mathematical language and representation were the dominant difficulties in solving word problems for students in elementary school. The research aims to analyze students' mathematical language and representation difficulties when solving word problems. The research subjects were 114 fifth-grade elementary school students selected using a purposive sampling technique with different mathematical abilities. The research was conducted at an elementary school in Sumbawa District, West Nusa Tenggara, Indonesia. Data collection techniques included tests, questionnaires, and interviews. The research results show that students' difficulties in mathematical language were dominant indicators of sentences. Students had difficulties in mathematical representation indicators, which were dominant in symbols. The factors that cause difficulty for high, middle, and lower ability students are unaccustomed to solving word problems and using problem-solving procedures, difficulty with concepts, difficulty with reasoning, difficulty understanding what is known and what is being asked, not being careful in reading the problem, and difficulty with long sentences. Student word problem-solving is in the low category.